Determinants of menstrual hygiene management among adolescents: The interplay of school sanitation infrastructure and psychosocial support in Indonesia - Putri Azzahroh; Arfiani Dean Putri; Febry Mutiariami Dahlan (Nursing and Health Sciences Journal (NHSJ), 2026)
Suboptimal Menstrual Hygiene Management significantly increases the risk of reproductive tract infections among adolescent girls globally, representing a major public health challenge. External environmental and psychosocial determinants critically shape these vital health practices during the developmental transition. This study aimed to analyze the correlations between school sanitation facilities, peer roles, and family support regarding the menstrual hygiene behavior of female students at a vocational high school in Bekasi City. Researchers employed a quantitative analytical approach utilizing a cross-sectional design. The study population comprised 93 female students who had experienced menarche, selected through a total sampling technique. Primary data collection involved a validated structured questionnaire. Statistical analysis used the Chi-Square test to assess the significance of the relationship between the independent and dependent variables. The findings revealed that 71.0% of respondents practiced good menstrual hygiene. Bivariate analysis demonstrated statistically significant correlations between school sanitation facilities (p=0.016), peer roles (p=0.039), and family support (p=0.015) with overall hygiene behavior. School sanitation facilities emerged as a dominant enabling factor influencing the consistency of hygiene practices within the educational environment. Optimal menstrual hygiene management requires a synergistic integration of adequate gender-responsive physical infrastructure and robust psychosocial support systems. Educational institutions and public health policymakers must prioritize both ongoing facility maintenance and comprehensive community-based reproductive health education to safeguard adolescent reproductive well-being and ensure equitable health outcomes.